ADVANCING ESL INSTRUCTION THROUGH COMMUNICATIVE PEDAGOGY: A COMPREHENSIVE ANALYSIS (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2026)
This study explores the effectiveness of communicative pedagogy in English as a Second Language (ESL) classrooms, focusing on its role in enhancing learners’ communicative competence and overall language proficiency. In the context of globalization, the demand for practical language skills has increased, requiring a shift from traditional teacher-centered approaches to more interactive and learner-centered methodologies.